Factors Correlating with Adoption of Systems Integration of Paddy- Livestock in Central Sulawesi Provinsi, Indonesia - Anna Fatchiya; Istiqlaliyah Muflikhati; Tatie Soedewo (Jurnal Penyuluhan, 2018)
The Indonesian government has introduced paddy-livestock integration into the farming community. However, the rate of adoption by farmers did not experience a significant increase. So the purpose of this study was to analyze the factors influencing  farmers' adoption level on technological innovation in the paddy-livestock integration system.  The data collection was conducted by Focus Group Discussion (FGD) to get qualitative data and surveys for quantitative data. FGDs were conducted in three locations: in the two villages of research with farmers groups, and in AAAT. The survey uses a questionnaire with a volume of about 120 people in two villages respectively were 60. Data were analyzed descriptively (sum, the average, and percentage) and tested with Spearman Rank correlation.  Processing data by software Exel and SPSS ver 16.  The research showed that the internal factors of farmers, the characteristics of innovation, and external support related to the phase (knowledge, interest, and adoption) of farmers' adoption of the technology innovation of paddy-livestock integration system in the form of fermented feed and organic fertilizer.Keywords:  adoption, innovation, integrated farming, livestock, paddy